2020
DOI: 10.1089/cyber.2019.0652
|View full text |Cite
|
Sign up to set email alerts
|

High Esteem and Hurting Others Online: Trait Sadism Moderates the Relationship Between Self-Esteem and Internet Trolling

Abstract: Internet trolling is commonly defined as disruptive online behavior, intended to provoke and distress others for amusement. Previous research has shown that gender (specifically, male), trait psychopathy, and trait sadism significantly predict engaging in trolling. In this study, we sought to replicate and extend previous research by exploring the role of self-esteem in predicting trolling, and possible interactions between self-esteem and personality. Participants (n = 400, 67.5 percent women, average age = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…We found that for adolescents, high psychopathy both correlated with and uniquely predicted increased incidence of trolling. This finding is consistent with results of adult samples [ 9 , 13 , 30 ], and in line with previous research that found adolescents with high psychopathy were more aggressive online [ 37 ]. For adolescents, the combination of a grandiose sense of self-worth and manipulative behaviour (i.e., interpersonal psychopathy), poor behavioural control and delinquency (i.e., behavioural psychopathy), and a lack of remorse and guilt (i.e., affective psychopathy) predicts higher trolling.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that for adolescents, high psychopathy both correlated with and uniquely predicted increased incidence of trolling. This finding is consistent with results of adult samples [ 9 , 13 , 30 ], and in line with previous research that found adolescents with high psychopathy were more aggressive online [ 37 ]. For adolescents, the combination of a grandiose sense of self-worth and manipulative behaviour (i.e., interpersonal psychopathy), poor behavioural control and delinquency (i.e., behavioural psychopathy), and a lack of remorse and guilt (i.e., affective psychopathy) predicts higher trolling.…”
Section: Discussionsupporting
confidence: 93%
“…Broadly, trolling has been adopted as an umbrella term to describe a range of antisocial deviant online behaviours [10]. In the current study, we follow previous empirical definitions where trolling is conceptualised as a disruptive online behaviour intended to provoke and distress others for one's own amusement [11][12][13]. Early conceptualisations of trolling outlined four main characteristics of the online behaviour: Deception, aggression, disruption, and success [14].…”
Section: Internet Trolling: Definition and Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, psychological theorizing (see Baumeister & Campbell, 1999) suggests that sadism is a self-protective mechanism whereby the pleasure derived from hurting others serves to offset the visceral disgust and distress associated with performing violent behavior. Consistent with that view, studies have shown the relationship between sadism and internet trolling (i.e., hurting others online) is stronger for individuals with high self-esteem (March & Steele, 2020) and sadism tends to be exacerbated when people are experiencing threats to the self (Pfattheicher & Schindler, 2015). Overall then, there is evidence from two different literatures indicating that OP and sadism are related to self-protection.…”
Section: Discussionmentioning
confidence: 75%
“…In the present research, we aim to explore the social psychological underpinnings of Internet trolling, a type of harmful online activity that may cause undesirable long-term consequences for Internet users by, for example, creating a hostile online environment and polarising opinions (Coles & West, 2016). Vast line of research shows that Internet trolling behaviors are related to antagonistic personality traits, low self-esteem, and a heightened level of negative mood (Buckels et al, 2014;Cheng et al, 2017;March, 2019;March & Steele, 2020). However, the psychological mechanisms behind these associations are less well understood.…”
Section: Introductionmentioning
confidence: 99%